2020
DOI: 10.3390/foods9101449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Nutritional Support System (Diet and Supplements) for Improving Gross Motor Function in Cerebral Palsy: An Exploratory Randomized Controlled Clinical Trial

Abstract: Background: Most patients with cerebral palsy (CP) do not respond to physical therapy due to deterioration in their nutritional status, secondary to gastrointestinal disorders and the catabolic state of the disease itself. However, basic treatments only contemplate the energy requirements and do not consider supplementation with glutamine, zinc, selenium, colecalciferol, spirulina, omega 3 or even vegetal proteins. Objective: In this study, we determined the effect of using a nutritional support system (NSS): … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Four studies presented some concerns only in one domain (bias in selection of the reported results) [7,12,21,23]; two presented some concerns in two domains [22,28]; and four presented some concerns in three domains [11,20,26,29]. In the five studies with high-risk domains, three presented high risk in only one domain [19,25,27], and two studies presented high risk of bias for two domains [10] (Fig 2B).…”
Section: Plos Onementioning
confidence: 98%
See 2 more Smart Citations
“…Four studies presented some concerns only in one domain (bias in selection of the reported results) [7,12,21,23]; two presented some concerns in two domains [22,28]; and four presented some concerns in three domains [11,20,26,29]. In the five studies with high-risk domains, three presented high risk in only one domain [19,25,27], and two studies presented high risk of bias for two domains [10] (Fig 2B).…”
Section: Plos Onementioning
confidence: 98%
“…Three studies evaluated other outcomes, comprising gross motor function, iron deficiency anemia and feeding skills. Aiming to improve gross motor function, Leal-Martinez et al (2020) [27] compared a nutritional support system with the diet recommended by the World Health Organization (WHO) and an observational group of patients between 4 and 12 years old. The…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…With the extreme shortage of trained professionals including dietitians, in addition to the limited availability and accessibility to institutionalized intervention programs in LMICs [ 13 ], it is likely that not all the interventions found effective in HIC settings may be applicable in LMIC settings. In absence of optimal management, these children are at high risk of malnutrition, which can in turn impact their functional outcomes, quality of life, and survival [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Leal-Martinez et al (2020) is an exploratory randomized controlled clinical trial investigating the effects of a nutritional support system for improving motor function in children living with cerebral palsy (CP) in Mexico [ 5 ]. CP is one of the most common disabilities in childhood and changes to gross motor function is one of the main characteristics associated with this disease that can contribute to malnutrition in patients with CP.…”
mentioning
confidence: 99%